Penggunaan Kursi Ergonomis untuk Mengurangi Keluhan Nyeri Otot Rangka (Musculoskeletal Disorders) pada Pekerja Laundry di Wilayah Kota Yogyakarta - Dian Sugesti Ningsih; Lucky Herawati; Agus Suwarni (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Musculokeletal disorders is a pain at parts of skeletal muscles felt by a person which is caused by various factors, either internal or external. Musculoskeletal disorders is a common health problem found in industrial sectors, included in the informal ones, such as in laundry business. Ironing process in laundry activities takes long duration and is a monotonous work. Many workers experiencing pain in their skeletal muscle after ironing, of which ergonomic factor is considered as one of the causes. Therefore, the research was intended to study about the application of ergonomic chair in reducing the musculoskeletal disorders among laundry workers in Yogyakarta city by conducting a true experiment with pre-test post-test with control group design. As thestudy subjects were 30 ironing workers taken from 30 laundry services selected as the sample. They were then divided equally into two groups, i.e. 15 were allocated both in the treatment and the control groups. Proportional cluster random technique was used in the sampling process. The measurement of musculoskeletal pain employed a 15 item questionnaire based on the Nordic Body Map questionnaire. The data then were analyzed by using Mann-Whytney test with ?=0,05 and obtained a p-value of 0,0001 which shows that the pain difference between the control and the treatment groups was significant. In the treatment group, after using the ergonomic chairs, the pain was felt decrease at waist, back, left hand and left foot; meanwhile in the control group, the measurement results in pre-test and post-test were similar. Based on the results, it is advised that coordination between the Licensing Office and laundry owners is needed to provide ergonomic chairs for the workers to work comfortably and to avoid the muscular skeletal disorders. For further studies it is recommended to consider nutritional status, psychological state and workload of the workers when applying the ergonomic chairs.